Demon Copperhead : A Novel - Kingsolver, Barbara (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2022)
The teenage son of an Appalachian single mother who dies when he is eleven uses his good looks, wit, and instincts to survive foster care, child labor, addiction, disastrous loves, and crushing losses
Text in English
BPL: David Winn Bishop and Isabel MacPherson Bishop Memorial Fund.
Keywords: Teenage boys -- Fiction; Orphans -- Fiction; Opioid abuse -- Fiction; Lee County (Va.) -- Fiction; Bildungsromans; Novels